Factors Impacting on Capital Structure of The UK listed Companies: Empirical Analysis - Chen, Hao (2010)
This paper investigates the potential factors that affect the choice of capital structure by analysing a panel of 150 listed UK companies for the period from 1999 to 2008, giving a total 1500 firm-year observations. Pooled regression estimation was first applied to the study, under the assumptions that there was no effect from firms or time. However, by running the Fixed Effect Model with industry dummy variables, it can be seen that some of the coefficient signs for the industries are significant. This indicated that the effect of industry is significant. Thus, Fixed Effect Model is adopted for the analysis in this study. Nine explanatory variables have been selected to measure their effect on leverage ratio. Five out of the nine variables are significantly related to leverage ratio while the rest four variables show that there are not very strong relationships between neither of them and the debt ratio. Mainly, the results support the prediction of trade-off theory in term of Tangibility variable and the Non-debt Tax Shield variable, but the earning volatility variables fail to confirm to trade-off theory. Moreover, profitability (measured by cash flow margin) failed to validate the predictions of pecking order theory whereas the growth opportunities variable rejects the agency theory hypothesis. In addition, the significant positive result of Tangibility proves the prediction of agency theory. Size variable confirms to both the prediction of trade-off theory and to information asymmetry theory.